Prospect theory and IPO returns in China - Wang, Zhiqiang; Su, Bingbai; Coakley, Jerry; Shen, Zhe (Journal of Corporate Finance, 2018)
This paper provides a new cumulative prospect theory (PT) perspective on IPOs by proposing a median-based expected skewness measure as the reference point for potential investors. Since our sample of 837 book-built Chinese IPOs over the 2006–2012 period comprises of 30% negative and 70% positive skewness issues, this paper reveals novel findings on the left-skewed IPOs that enjoy a mean first-day return of 65.61% compared with 56.55% for the right-skewed subsample. A one standard-deviation increase in skewness lead to an increase of 10.41 percentage points in the first-day return which is virtually 50% larger than that on right-skewed IPOs. While left-skewed IPOs exhibit a significantly positive relationship between offer price discounting and (absolute) skewness, the relationship for right-skewed IPOs is insignificant. A one-standard-deviation shock to skewness deepens discounting by left-skewed IPOs by 21.21 percentage points, making such IPOs susceptible to nominal price illusion. A skewness shock attracts more than double the mean value of retail orders to the left- than to the right-skewed subsample although the latter attracts 26% more investors. Prospect theory suggests that investors in left-skewed IPOs tend to flip to exploit the deep discounting (relative to their underlying value) on the first trading day rather than gamble on possible long run gains. Relatedly, their long run return measures are independent of absolute skewness but we find significantly inverse relationships between these variables for right-skewed IPOs. Overall, our PT framework provides the basis for a more nuanced picture of the motives for IPO investment and their contrasting implications for initial and long run returns.